Abilities of Physics Education Students in Constructing Graphics Based on Practicum Results and in Interpreting It - Hariawan, Hariawan; Muslimin , Muslimin; Werdhiana, I Komang (Universitas Tadulako, 2019)
The skills to construct and interpret graphs are a form of science skills and are an important component in learning physics. The purpose of this study was to describe the ability of undergraduate physics education students to construct graphs based on practicum data and interpret them. Data obtained through respondent answer sheets, thinking-aloud recordings, and interviews. The research was conducted at the Faculty of Teacher Training and Education (FKIP) Untad and the research subjects of the Physics Education Study Program students were 6 people obtained based on the values of Basic Physics I and Basic Physics practicum II then divided into three groups of levels (high, medium, and low) with each category as many as 2 people. The results of this study indicate: 1) in general, respondents in the high, medium, and low categories can construct graphs but are not based on the prerequisite ability to construct graphs, especially in determining the x-axis and y-axis variables, 2) on the ability to interpret graphs, respondents can interpret graphs the relationship between variables on the graph but not supported by an explanation or evaluation based on proper physics concepts, 3) The strategy used by respondents in constructing graphs, in general, is to convert data in decimal form or scientific notation and 4) The difficulties experienced by respondents when constructing graphs are converting data, determining the scale and how to determine the variables on each graph axis.